The bioelectric well: a novel approach for in situ treatment of hydrocarbon‐contaminated groundwater. Issue 1 (11th July 2017) - Palma, Enza; Daghio, Matteo; Franzetti, Andrea; Petrangeli Papini, Marco; Aulenta, Federico
Summary: Groundwater contamination by petroleum hydrocarbons (PHs) is a widespread problem which poses serious environmental and health concerns. Recently, microbial electrochemical technologies (MET) have attracted considerable attention for remediation applications, having the potential to overcome some of the limiting factors of conventional in situ bioremediation systems. So far, field‐scale application of MET has been largely hindered by the limited availability of scalable system configurations. Here, we describe the 'bioelectric well' a bioelectrochemical reactor configuration, which can be installed directly within groundwater wells and can be applied for in situ treatment of organic contaminants, such as PHs. A laboratory‐scale prototype of the bioelectric well has been set up and operated in continuous‐flow regime with phenol as the model contaminant. The best performance was obtained when the system was inoculated with refinery sludge and the anode potentiostatically controlled at +0.2 V versus SHE. Under this condition, the influent phenol (25 mg l −1 ) was nearly completely (99.5 ± 0.4%) removed, with an average degradation rate of 59 ± 3 mg l −1 d and a coulombic efficiency of 104 ± 4%. Microbial community analysis revealed a remarkable enrichment of Geobacter species on the surface of the graphite anode, clearly pointing to a direct involvement of this electro‐active bacterium in the current‐generating and phenol‐oxidizing process. Abstract : Here we describe the "Bioelectric Well" a bioelectrochemical reactor configuration, which can be installed directly within groundwater wells and can be applied for in situ treatment of organic contaminants, such as petroleum hydrocarbons. The performance of a lab‐scale prototype of the bioelectric well was assessed using phenol as model groundwater contaminant. Geobacter species enriched over the surface of the graphite anode, clearly pointing to a direct involvement of this electro‐active bacterium in the current‐generating and phenol‐oxidizing process.